Effects of body mass index on urinary lithogenic factors in urinary system stone patients - Yavuz Güler (Folia Medica, 2024)
Aim: Obesity and metabolic syndrome are becoming more prevalent these days. In addition, we know that urinary stone disease is also on the rise. In this study, we wanted to examine if body mass index (BMI) had a negative effect on the stone disease by evaluating 24-hour urinalysis in stone patients and recurrence rates in our region. Materials and methods: From January 2017 to December 2019, a total of 193 patients were assessed retrospectively in terms of their 24-hour urine analysis results and blood parathyroid hormone (PTH) values. These patients were divided into 3 groups by their BMI <25, 25-30, and ≥30 (group 1, 2, and 3, respectively). Demographic and 24-hour urine analysis data were compared between the groups. Patients with and without recurrent stones were divided into 2 groups and lithogenic factors were analyzed. Possible lithogenic risk factors for recurrent stone formation were examined in a multivariate logistic regression analysis. Pearson and Spearmen correlation analysis was used for correlation. Results: Groups 1, 2, and 3 had 107, 55, and 31 patients, respectively. There was a statistically significant difference between the groups in their BMI, diabetes mellitus (DM), hypertension (HT), gout, spontaneous stone passage, and extracorporeal shock wave lithotripsy (ESWL) factors. While the mean of BMI was similar for groups 2 and 3, the mean of group 1 was statistically significantly lower. Group 3 exhibited statistically significant higher rates of DM, HT, and gout diseases in comparison to the other groups. ESWL and spontaneous stone removal factors were statistically significantly higher in groups 2 and 3 than in group 1. According to the results of the 24-hour urine analysis, the urinary pH, uric acid, calcium, oxalate, and phosphate values were statistically different in group 1 from other groups. Urinary pH was more acidic and uric acid, calcium, oxalate, and phosphate values were higher in groups 2 and 3. Only BMI was statistically different from the lithogenic factors in the patient groups with and without recurrent stones. Also, in the multifactorial logistic regression analysis, BMI factor was found to be significant in duplicate stone formation. There was a weak but statistically significant correlation between the amount of uric acid and stone volume (r=0.307, p=0.04). Conclusion: Increased BMI negatively affects the lithogenic factors in urine and facilitates the formation of recurrent stones.